Parental Involvement During Online Learning: A Study Among Low-Income Families in Indonesia - Risa Fitria; Aulia Putri Pangesti (Jurnal Ilmiah Sekolah Dasar, 2023)
Most parents face problems during the pandemic, especially low-income parents face tougher challenges than others. This study aims to analyze how parents with low economic status get involved in their children's learning amidst the pandemic and what the low-income parents’ perspectives on online learning amidst the pandemic were. This research used a survey research method to obtain the data from one of the public schools. Questionnaire consisting of quantitative and qualitative data was used and disseminated via Google Forms to all the parents in one primary state school. This study is involving 132 parents. The data were then analyzed by using descriptive analysis. As a result, the study showed that the parents who were primarily categorized as economically disadvantaged status were involved in their children's learning in various ways, such as explaining, completing, and checking their child's worksheets or assignments. This study also found indication that low-income parents faced difficulties in assisting their children during online learning, making most parents resistant to online learning. Finally, this study suggested several recommendations to policymakers and educators for future consideration.